Anteromedial versus trans-tibial technique for anterior cruciate ligament reconstruction using quadrupled hamstring graft: a comparative study - Singh, Barunkumar; Gaurav, Sharma; Akshay, Bhardwaj (International Journal of Research in Orthopaedics, 2019)
Background: Femoral tunnel position plays a pivotal role for successful outcome in anterior cruciate ligament (ACL) reconstruction surgeries. Recently, the anteromedial techniques have gained popularity over the trans-tibial technique due to better anatomical position and better stability rotationally and antero-posteriorly then the later. The aim of the present study was to compare the technical difficulty and ease, functional and radiological outcome of trans-tibial and anteromedial portal techniques in ACL reconstruction. Methods: Thirty patients between March 2015 and February 2016 with ACL tear underwent arthroscopic reconstruction using quadrupled hamstring graft and were divided into two groups A (anteromedial) and group B (trans-tibial) as per the technique used. Patients with multiligament injuries, revision surgeries, and osteoarthritis knee were excluded. All the patients were followed-up for 24 months and clinical Lysholm and IKDC scores along with radiological outcome were calculated. Results: The mean age of patients were 32.4±6.3 years. Isolated ACL tear was seen in 16 (53.4%) cases followed by medial meniscus injury in 11 (36.6%) patients. The mean duration between injury and surgery was 14.8±8.99 and 21.6±3.23 days in group A and B respectively (p=0.0122). The radiological position of femoral tunnel in sagittal and coronal plane was statistically significant in both the groups. The Lysholm and IKDC scores showed statistically significant difference at 3 months post-operatively. Conclusions: Anteromedial and trans-tibial techniques have similar long term functional outcomes. However, more anatomical position of the graft through the anteromedial technique and better rotational and anteroposterior stability makes it theoretically to be superior to the trans-tibial technique.